2008
DOI: 10.1016/j.biocel.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Low and high affinity receptors mediate cellular uptake of heparanase

Abstract: Heparanase is an endoglycosidase which cleaves heparan sulfate and hence participates in degradation and remodeling of the extracellular matrix. Importantly, heparanase activity correlated with the metastatic potential of tumor-derived cells, attributed to enhanced cell dissemination as a consequence of heparan sulfate cleavage and remodeling of the extracellular matrix barrier. Heparanase has been characterized as a glycoprotein, yet glycan biochemical analysis was not performed to date. Here, we applied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…Apart of HSPGs, several cell surface proteins have been shown to bind heparanase and mediate its uptake. These include mannose 6-phosphate receptor (MPR) and low density lipoprotein receptor-related protein (LRP) (Ben-Zaken et al, 2008; Vreys et al, 2005) which potentially can mediate heparanase signaling and non-enzymatic effects. The existence of cell surface heparanase receptor(s) is supported by binding experiment, reinforcing the notion that while HSPGs serve as low affinity, high abundant binding sites, heparanase also associates with high affinity, low abundant cell surface receptor(s) (Ben-Zaken et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Apart of HSPGs, several cell surface proteins have been shown to bind heparanase and mediate its uptake. These include mannose 6-phosphate receptor (MPR) and low density lipoprotein receptor-related protein (LRP) (Ben-Zaken et al, 2008; Vreys et al, 2005) which potentially can mediate heparanase signaling and non-enzymatic effects. The existence of cell surface heparanase receptor(s) is supported by binding experiment, reinforcing the notion that while HSPGs serve as low affinity, high abundant binding sites, heparanase also associates with high affinity, low abundant cell surface receptor(s) (Ben-Zaken et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Heparanase, instead, adopted somewhat different trafficking route. Notably, the ∼65 kDa latent enzyme gets secreted despite the presence of mannose-6-phosphate modification [101], internalized by cellular uptake and accumulates in lysosomes [44] (see below). This uncommon trafficking route may be explained by non enzymatic function of the latent enzyme extracellularly.…”
Section: Post-transcriptional Regulation Biosynthesis Trafficking mentioning
confidence: 99%
“…Latent heparanase secretion is directed by an Nterminal signal peptide (Met 1 -Ala 35 ). The secreted protein interacts rapidly and efficiently with cell surface HSPGs, low density lipoprotein receptor-related protein, and MPR [101,119,120], followed by internalization and processing, collectively defined as heparanase uptake [44,101,119]. Following uptake, heparanase was noted to reside primarily PKC/PKA within endocytic vesicles identified as late endosomes and lysosomes [121,122].…”
Section: Heparanase Processing and Activation By Cathepsin Lmentioning
confidence: 99%
“…A number of studies have shown that secreted or exogenously added latent heparanase rapidly interacts with normal and tumor-derived cells, followed by internalization and processing into a highly active enzyme (Ben-Zaken et al, 2008; Gingis-Velitski et al, 2004a; Gingis-Velitski et al, 2004b; Nadav et al, 2002; Vreys et al, 2005; Zetser et al, 2004), collectively defined as heparanase uptake. Several approaches, including HS-deficient cells, addition of heparin or xylosides, and deletion of HS-binding domains of heparanase, provided compelling evidence for the involvement of HS in heparanase uptake (Gingis-Velitski et al, 2004b; Levy-Adam et al, 2005).…”
Section: Cellular Uptake and Trafficking Of Heparanasementioning
confidence: 99%